Leadership in turbulent times - Goodwin, Doris Kearns (Simon & Schuster, 2018)
"In this culmination of five decades of acclaimed studies in presidential history, Pulitzer Prize-winning author Doris Kearns Goodwin offers an illuminating exploration of the early development, growth, and exercise of leadership. Are leaders born or made? Where does ambition come from? How does adversity affect the growth of leadership? Does the leader make the times or do the times make the leader? In Leadership, Goodwin draws upon the four presidents she has studied most closely--Abraham Lincoln, Theodore Roosevelt, Franklin D. Roosevelt, and Lyndon B. Johnson (in civil rights)--to show how they recognized leadership qualities within themselves and were recognized as leaders by others. No common pattern describes the trajectory of leadership. Although set apart in background, abilities, and temperament, these men shared a fierce ambition and a deep-seated resilience that enabled them to surmount uncommon hardship. At their best, all four were guided by a sense of moral purpose. At moments of great challenge, they were able to summon their talents to enlarge the opportunities and lives of others. This seminal work provides an accessible and essential road map not only for aspiring and established leaders in every field but for all of us in our everyday lives. In today's polarized world, these stories of authentic leadership in times of fracture and fear take on a singular urgency."--Provided by publisher.